Does air pollution exposure affect semen quality? Evidence from a systematic review and meta-analysis of 93,996 Chinese men - Junjie Liu; Yanpeng Dai; Runqing Li; Jiayi Yuan; Quanxian Wang; Linkai Wang (Frontiers Media S.A., 2023)
BackgroundAir pollution may impair male fertility, but it remains controversial whether air pollution affects semen quality until now.ObjectivesWe undertake a meta-analysis to explore potential impacts of six pollutants exposure during the entire window (0-90 days prior to ejaculation) and critical windows (0-9, 10-14, and 70-90 days prior to ejaculation) on semen quality.MethodsSeven databases were retrieved for original studies on the effects of six pollutants exposure for 90 days prior to ejaculation on semen quality. The search process does not limit the language and search date. We only included original studies that reported regression coefficients (β) with 95% confidence intervals (CIs). The β and 95% CIs were pooled using the DerSimonian-Laird random effect models.ResultsPM2.5 exposure was related with decreased total sperm number (10-14 lag days) and total motility (10-14, 70-90, and 0-90 lag days). PM10 exposure was related with reduced total sperm number (70-90 and 0-90 lag days) and total motility (0-90 lag days). NO2 exposure was related with reduced total sperm number (70-90 and 0-90 lag days). SO2 exposure was related with declined total motility (0-9, 10-14, 0-90 lag days) and total sperm number (0-90 lag days).ConclusionAir pollution affects semen quality making it necessary to limit exposure to air pollution for Chinese men. When implementing protective measures, it is necessary to consider the key period of sperm development.